1988
DOI: 10.1111/j.1432-1033.1988.tb14230.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural requirements of lipid A species in activation of clotting enzymes from the horseshoe crab, and the human complement cascade

Abstract: The structure/activity relationship of lipid A, a bioactive center of endotoxic lipopolysaccharides, in the activation of the clotting enzyme cascade of a horseshoe crab amoebocyte lysate (Limulus activity) and the complement system in human serum, was examined using synthetic lipids A and related compounds. Regarding Limulus activity, a newly developed colorimetric method, which utilizes a mixture of recombined clotting factors and a chromogenic substance, was much more sensitive for detecting changes in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
48
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 28 publications
4
48
0
Order By: Relevance
“…For an understanding, the structural requirements of the activation of the clotting cascade must be considered. By using different synthetic lipid A and part structures, Takada et al [31] have shown that the monophosphoryl 4'-phosphate lipid A has the same activity as bisphosphoryl lipid A, whereas the monophosphoryl 1-phosphate lipid A has strongly reduced activity. We have found that the interaction of LPS and lipid A with hemoglobin [32] or albumin [33] led to a strong or slight increase, respectively, of the cytokine production in mononuclear cells, but was not correlated with the results in the Limulus test, which exhibited somehow non-systematic variations.…”
Section: Discussionmentioning
confidence: 99%
“…For an understanding, the structural requirements of the activation of the clotting cascade must be considered. By using different synthetic lipid A and part structures, Takada et al [31] have shown that the monophosphoryl 4'-phosphate lipid A has the same activity as bisphosphoryl lipid A, whereas the monophosphoryl 1-phosphate lipid A has strongly reduced activity. We have found that the interaction of LPS and lipid A with hemoglobin [32] or albumin [33] led to a strong or slight increase, respectively, of the cytokine production in mononuclear cells, but was not correlated with the results in the Limulus test, which exhibited somehow non-systematic variations.…”
Section: Discussionmentioning
confidence: 99%
“…The most widely employed test for the presence of endotoxin in fluids is based on LPS sensing by the clotting system of the horseshoe crab. This assay is not specific for hexaacyl LPS (132,133). LPS recognition by the horseshoe crab likely evolved as a defense from aquatic bacteria; the assay's ability to recognize widely diverse lipid A structures enhances its ability to detect environmental contamination of biologicals, but it also may account for some of the problems observed when the test has been used to detect endotoxemia and gram-negative bacteremia in human patients (the correlations between disease severity, gram-negative bacteremia and endotoxemia have generally been poor) (57).…”
Section: Limitations Possible Implicationsmentioning
confidence: 97%
“…Degradation by chemical means showed that upon treatment with mild aqueous acid, a precipitate could be obtained which was termed lipid A and represents the lipid anchor of the LPS molecule in the outer membrane (Westphal and Lu¨deritz, 1954;Imoto et al, 1985), and which was later on identified as the endotoxic principle of LPS (Lu¨deritz et al, 1984;Galanos et al, 1985;Kotani et al, 1985). A detailed investigation of structure-activity relationships (Kotani et al, 1984;Takada et al, 1988;Rietschel et al, 1994), including a biophysical characterization of biologically active and inactive lipid A revealed structural parameters which influence the biological activities of LPS (Rietschel et al, 1990;Seydel et al, 1999).…”
Section: Article In Pressmentioning
confidence: 98%